A MIMO-Enabled Free Space Optical Link under Log-Normal Fading/Gamma-Gamma Channel: Exploring an Optimal Modulation Scheme - Haroun Errachid Adardour; Samir Kameche; Mehtab Singh (International Journal of Optics)
The technology of free-space optical communication (FSOC) systems has some distinctive merits compared to other technologies. Its use is extremely beneficial to meet the exigencies of optical telecommunications and wireless networks (OTWNs). However, since the OTWNs transport a lot of data, the choice of a reliable modulation scheme is highly crucial. To this end, the focus of this paper is an in-depth study of a Point-to-Point Optical Link (P2P-OL) system under a FSOC-Multiple-Input Multiple-Output (MIMO) channel using an optimal modulation scheme. Furthermore, atmospheric turbulence (AT) effects over the FSOC-MIMO channel are incorporated in the proposed system to obtain substantial results. The performance analysis test of the proposed high-rate P2P-OL system is validated under the case that the channel decreases significantly when the AT gets strong regimes. Finally, the proposed system uses an optimal Non-Return to Zero Pulse Generator-Mach-Zehnder Modulator ((NRZPG-MZM)) scheme, which displays acceptable performance levels in a dust-fog meteorological environment under a LNF FSOC-9 × 9 channel with the attenuation value of 59.66 dB/km (i.e., max OSNR = 24.9 dB, min BER = 1e − 09, and max Q-factor = 6), whereas with the same environment under a G-G FSOC-9 × 9 channel, the attenuation value is 58.55 dB/km (i.e., max OSNR = 24.67 dB, min BER = 1e − 09, and max Q-factor = 6).